PENGARUH PERILAKU APARATUR TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR CAMAT BUNTA KABUPATEN BANGGAI - Rahmad, Rahmad (Katalogis, 2014)
The  Influence  of  Apparatus’  Behaviour  to  Service  Quality  at  Bunta  District  BanggaiRegency). This research was aimed to study and analyze : 1) the apparatus’ behaviour to service quality at Bunta Sub-district; 2) the dominant factors that influence the apparatus’ behavior to service quality at Bunta at Sub-district.  Adopted fromthe theory Siagian S.P and Ndraha T. The population  of  this  study  the  sub  district  apparatus,  Sub-village,  Village,  and  all  communities involved  2.369  people.    Sample was  drawn  through  purposive sampling.    The sample of  this research was gathered  from 3 group communities; 3  (three) villages and 1  (one) Sub-village located at Bunta district consisted 50 people and the head of Sub-village, head of Village, and staff of district of Bunta as respondent.   The data collection was conducted through observation, questionnaire , interview, and documentation, while the data was analysis through quantitative, frequently table and percentage table.  The study result shows that the service quality of Apparatus of district Bunta Banggai Regency still not good.